Exploring women’s cultural experiences during pregnancy and childbirth among the Kalenjin in Kenya : towards a culturally driven safe care framework - Kemboi-Ngotie, Teckla Jebiwot (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.